Parody in two novels by De Santis, El enigma de Paris and Crimenes y jardines - Casillo, Ines (Romanica Olomucensia, 2019)
In this study, the ways in which De Santis parodies the crime novel in his two novels El enigma de Paris (2007) and Crimenes y jardines (2013) and how parody results in a fantastic text are traced. In the first part, both the framework of the two novels and the theory of irony and of parody will be presented. The structural use of ironic incongruity is seen as a characteristic of parody which differentiates it from other forms of literary imitation or metafiction: the form which is used by parody is always humorous. In the second part, different texts will be analysed, with the analysis being organized according to recurrent themes which are the objects of irony. Later, in the results, how the author uses different types of irony to parody criminal novels and realism in fiction will be shown. The text is composed as a meeting place, in which the author communicates with his reader, who is invited to play with him. In the conclusion, the thesis is proposed that the whole text is used in an ironic-humorous way, which destabilizes the genre chosen by the author as the form of his novels. The abundant ironies transform the text into a non-real, extremely artificial discourse. The fantastic is created by the constant and growing use of irony throughout the whole text. The experimental tone of this kind of fiction is emphasized by the rupture with reality, which is a characteristic of fantastic literature.
Keywords: irony; parody; humour; crime literature; realism; fantastic fiction in El Rio de la Plata